The “Mohazell” herbal formula in combination with a calorie-restricted diet can improve systemic inﬂammation in obesity: a randomized double-blind, clinical trial - Valizadeh, Eynollah; Akbari, Hossein; Ghalichi, Faezeh; Ostadrahimi, Alireza (Progress in Nutrition, 2019)
Inﬂammation is one of the primary mechanisms involved in the development of metabolic complications. The aim of the present study was to determine the effects of “Mohazell”, a traditional herbal formula consisting of Origanum vulgare, Carumcarvi, Trachyspermum copticum and Ruta Graveolen in combination with a calorie-restricted diet on biomarkers of systemic inﬂammation in obese adults. In this double-blind placebo-controlled randomized clinical trial, 68 volunteer obese (Body mass index: 30–35 kg/m2) subjects aged 25–50 years were recruited. Participants were randomly divided into two groups, an intervention group (n=34) and a placebo group (n=34). Each group received either: (1) a low-calorie diet with 3 g/day of ‘Mohazell’ or (2) a low-calorie diet with 3 g/day placebo for 8 weeks. Patients weight was measured, their BMI was calculated and biochemical parameters such as high Sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α) and IL-6 were measured at baseline and after the intervention. No side effects were reported with the ‘Mohazell’ supplementation. ‘Mohazell’ decreased serum levels of TNF-α (p=0.001) and hs-CRP (p=0.04) in the treatment group. Also, IL-6 decreased insignificantly in both groups (p=0.78). Additionally, significant reductions were observed for weight, BMI, Energy and macronutrients (p<0.05). There were statistically significant differences for weight (0.023), BMI (0.046) and TNF-α (0.001) in between group analysis. The ‘Mohazell’ supplementation combined with a calorie-restricted diet may modulate systemic inﬂammatory biomarkers in obese adults. However, more studies are needed to clarify the efﬁcacy of ‘Mohazell’ as an adjunct therapy to improve inﬂammatory parameters in obese subjects.